Research progress of gut microbiota and obesity caused by high-fat diet - Fan, Shuyi; Chen, Suyun; Lin, Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Obesity, a chronic metabolic disorder caused by an energy imbalance, has been increasingly prevalent and poses a global health concern. The multifactorial etiology of obesity includes genetics factors, high-fat diet, gut microbiota, and other factors. Among these factors, the implication of gut microbiota in the pathogenesis of obesity has been prominently acknowledged. This study endeavors to investigate the potential contribution of gut microbiota to the development of high-fat diet induced obesity, as well as the current state of probiotic intervention therapy research, in order to provide novel insights for the prevention and management of obesity.